The duration of reaching movement is longer than predicted by minimum variance - Wang,C; Xiao,Y; Burdet,E; Gordon,J; Schweighofer,N (Journal of Neurophysiology, 2016)
Whether the CNS minimizes variability or effort in planning arm movements can be tested by measuring the preferred movement duration and end-point variability. Here, we conducted an experiment in which subjects performed arm-reaching movements without visual feedback in fast, medium, slow, and preferred duration conditions. Results show that (i) total endpoint variance was smallest in the medium duration condition, and (ii) subjects preferred to carry out movements that were slower than this medium duration condition. A parsimonious explanation for the overall pattern of end-point errors across fast, medium, preferred, and slow movement durations is that movements are planned to minimize effort as well as endpoint error due to both signal-dependent and constant noise.